Termorregulação de cordeiros f1 (Dorper x Santa Inês) em ambiente equatorial: comportamento e respostas fisiológicas - Morais, Larissa Kellen da Cunha (2018)
The purpose of this study was to answer the following questions: How does the radiant thermal environment direct the behavioral activities of crossbred sheep managed in pasture in a semiarid equatorial environment? What level of radiation causes animals to stop grazing and seek shade? Furthermore, when exposed to radiation, is there preference over the azimuthal orientation of the animals? Twelve F1 lambs (Dorper x Santa Inês) with predominance of black and white fur and 18 ± 1.2 kg of body weight were randomly distributed in two pickets. The animals were managed from 06:00 to 17:00, recording the time spent feeding, rumination, leisure, standing, lying, exposed or protected from solar radiation, body orientation in relation to the sun's azimuth direction, respiratory rate and temperature of the surface of the pelt. The least squares method was used to test the effect of predominance of hair color, time classes and solar radiation on the behavioral and physiological variables. There was a variation (P <0.05) in lambs behavior from 06:00 to 16:00, the pattern of these changes being similar (P> 0.05) for fur animals with predominance of black and white meshes. As of 9:00 am, there was a decrease in the time spent with grazing activities and the animals began to increase the time spent in the shade, as well as, ruminating, lying down and at leisure. From 10:00 am to 11:00 am, the animals remained in the shade for approximately 70% of the time. From 11:00 a.m. to 12:00 p.m., grazing again became the main activity of the animals. There was no preference (P> 0.05) for body orientation in relation to the azimuthal direction of the sun. When the behavioral variables were evaluated as a function of the solar radiation classes, for lambs with predominance of black and white mesh, there was no change (P> 0.05) in the pattern of behavior of the animals. There was no difference (P> 0.05) in the respiratory rate for lambs with predominance of black and white fur. On the other hand, black-haired animals had a higher average surface temperature at practically all times evaluated. The behavioral activities of F1 lambs (Dorper x Santa Inês) managed to pasture were directed by a circadian pattern, using the meteorological conditions of this study. Radiation levels between 600 and 700 W.m-2 may have motivated lambs to stop grazing and seek shade. Animals have no preference for body orientation (parallel or perpendicular) in relation to the azimuthal direction of the sun.